The role of bicycles and bicycle empowerment centres in improving the mobility and livelihoods of the poor, and assisting with low-carbon development in Cape Town Michael Joseph Boulle - Boulle, Michael (Department of Social Development, 2014)
Includes abstract. Includes bibliographical references.